Emotional Competencies in the Training of Social Work Professionals - Concha Toro, Marcela del Carmen (2023)
Among all the consequences resulting from the COVID-19 pandemic and the socio-sanitary emergency context, the opportunity to make visible those changes required by the training and professional system to social workers stands out. An example of this consists of the need to reinvent this social field to provide new assistance and social intervention in crisis, which implies deploying its full potential to offer emotional support resources in situations of physical-social distancing under the modality of teleworking, in a state of confinement or return to the new normality. All these facts have been generating emotional exhaustion in this professional group and the student population in training. Therefore, this investigation aims to highlight the importance of emotional education and the formation of emotional competencies that strengthen the professional performance of future social workers, not only in an exceptional context but in any daily situation that requires their attention or intervention, especially since emotional competencies are directly related to social and cognitive skills, with the achievement of learning and with work results. As a main discovery, the investigators consider it essential to implement training programs that promote the development of emotional competencies, starting with a clear diagnosis that allows reorienting the teaching and learning process. Hence, it would be possible to contribute to the comprehensive training of future social work professionals. In addition, the authors conclude that emotional competencies represent an integral human growth that points both to an educational process in society and to lifelong learning. Moreover, this integrates learning to know, to do, to be, and to learn to live together. Finally, the researchers recommend that the incorporation of social emotional learning be gradual, continuous, and systematic. Furthermore, that a permanent training strategy aimed at teachers who train social work students be contemplated, and that a theoretical approach be integrated from the sociology of emotions that considers the sociocultural diversity of the environments and contexts in which they operate.